Prevalence of Recurrent Hospital Admission in Children with Recurrent Wheezing in Babylon Province - Falah, Sura; Mukhlif, Saad Fawwaz; Degan, Abeer (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Occurring of recurrent wheezing attacks signify a significant healthcare problem and considered one of the most common causes of emergency unit admission and hospitalizations. AIM: The aim of study is to determine the associations of recurrent hospital admissions in children with recurrent wheezing. METHODS: Cross-sectional descriptive study of 102 children with recurrent wheezy chest. Data collected from admitted patients with recurrent wheezing by direct interview with the patients’ families. Patients were 6 months to 5 years old. Data collected including age, gender, place of living whether urban or rural, prematurity, no. of people at home, history of NCU admission, history of ICU admission, exclusive breast feeding for 1st 6 months, anemia, GERD, history of atopy, exposure to smoking, inhaler use, and CXR findings. RESULTS: About 79.41% of children have 1-3 times admission in hospital, significant association between the no. of hospitalization and History of ICU admission, children with more than 3 times admission to hospital present with GERD with significant association. Significant association with more than 3 times admission to hospital have previous history of exposure to smoking, inhaler use and X-ray finding. CONCLUSION: One to three years old children is the most common age they have recurrent wheezing, most children with recurrent wheezy chest have more than 3 times hospitalization, most babies have previous history of ICU admission, GERD and exposure to smoking.